SWAMI VIVEKANANDA‟S VIEW ON KARMA AND MOKSA: A BRIEF DISCUSSION - Dutta, Rupjyoti (International Journal of Psychosocial Rehabilitation, 2020)
The concept of karma is a doctrine considered to be the foundation stone of entire Indian philosophical thought. The word ‘karma’ is derived from ‘kri’ dhatu of Sanskrit. Literally it means to do something. Metaphysically, it means which of our past actions were causes of our present state of affairs. The Indian solution of the great riddle of the origin of suffering and the diversity of human conditions is to be found in the word karma. The doctrine of karma and their retribution is of great antiquity in India. It gradually broke away from Vedic naturalism, mysticism and piety. As a man himself sows, so he himself reaps, no man inherits the good or evil act of another man. The fruit is of the same quality with the action good or bad, there is no destruction of the action.In Indian philosophy there are four Purusarthas. Among them,Moksa is considered as the highest end of life. It is used for various terms like- emancipation, enlightenment, liberation and release in different schools of Indian philosophy. It refers to freedom from samsara, the cycle of death and rebirth. According to the epistemological and psychological standpoint, moksa means freedom from ignorance, self- realisation, self-actualisation and self-knowledge.An attempt is made here to discuss how Vivekananda considers the notion of KARMA and MOKSA.